The power to comprehend with all the saints: the formation and practice of a pastor-theologian - Alston, Wallace M.; Jarvis, Cynthia A. (William B. Eerdmans Pub. Co, 2009)
Thegenesis of theological existence /Wallace M. Alston, Jr. --TheBible and theological formation : on becoming a theologian of the cross /V.F. (Bud) Thompson --Raising pastor-theologians : let the children say it first /Brant S. Copeland --Faith and college /Richard R. Crocker --Theeducation of a pastor-theologian : toward a learned ministry /Wallace M. Alston, Jr. --Therole of theological masters in the formation of the pastor-theologian /Cynthia A. Jarvis --Follow Him through the land of unlikeness : "passing over" as a way of truth in the practice of ministry /Albert H. Keller --Theliving edge of faith : doubt and skepticism in the formation of pastor-theologians /Rebecca Kuiken --Reading as habitus : on the formative practice of reading theology today /Kristine Suna-Koro --Of struggle, surrender, and spirit /Anita R. Warner --Theformative power of significant events /Robert C. Ballance --Thecall of a lifetime /W. Rush Otey III --Loving God with the mind and thinking with the heart : the pastor-theologian in the pulpit /John M. Stapleton --Therecovery of theological preaching /Wallace M. Alston, Jr. --Pastor and teacher : a way forward from the old congregational order /James L. Haddix --On not offering psychological banalities as God's word : a Reformed perspective on pastoral care /Cynthia A. Jarvis --Thetheological significance of administration in the pastoral ministry /Thomas W. Currie III --Formed by a lifetime of theological reflection and study /Allen C. McSween, Jr. --Thepastor as theologian of the sacraments : baptism /V. Bruce Rigdon --Thepastor as theologian of the sacraments : Holy Communion /V. Bruce Rigdon --Therole of the pastor-theologian in the evangelization of the church : a Wesleyan/Methodist way forward /Kenneth H. Carter, Jr. --Thepastoral prayer as a theological occasion /Scott Hoezee --Thepastor-theologian and death /Allen C. McSween, Jr. --Thesplendid embarrassment : theology's home and the practice of ministry /Thomas W. Currie III.